Garlic powder intake and cardiovascular risk factors: a meta-analysis of randomized controlled clinical trials - Kwak, Jin Sook; Kim, Ji Yeon; Paek, Ju Eun; Lee, You Jin; Kim, Haeng-Ran; Park, Dong-Sik; Kwon, Oran (Nutrition research and practice, 2014)
Although preclinical studies suggest that garlic has potential preventive effects on cardiovascular disease (CVD) risk factors, clinical trials and reports from systematic reviews or meta-analyses present inconsistent results. The contradiction might be attributed to variations in the manufacturing process that can markedly influence the composition of garlic products. To investigate this issue further, we performed a meta-analysis of the effects of garlic powder on CVD risk factors. We searched PubMed, Cochrane, Science Direct and EMBASE through May 2014. A random-effects meta-analysis was performed on 22 trials reporting total cholesterol (TC), 17 trials reporting LDL cholesterol (LDL-C), 18 trials reporting HDL cholesterol (HDL-C), 4 trials reporting fasting blood glucose (FBG), 9 trials reporting systolic blood pressure (SBP) and 10 trials reporting diastolic blood pressure (DBP). The overall garlic powder intake significantly reduced blood TC and LDL-C by -0.41 mmol/L (95% confidence interval [CI], -0.69, -0.12) (-15.83 mg/dL [95% CI, -26.64, -4.63]) and -0.21 mmol/L (95% CI, -0.40, -0.03) (-8.11 mg/dL [95% CI, -15.44, -1.16]), respectively. The mean difference in the reduction of FBG levels was -0.96 mmol/L (95% CI, -1.91, -0.01) (-17.30 mg/dL [95% CI, -34.41, -0.18]). Evidence for SBP and DBP reduction in the garlic supplementation group was also demonstrated by decreases of -4.34 mmHg (95% CI, -8.38, -0.29) and -2.36 mmHg (95% CI, -4.56, -0.15), respectively. This meta-analysis provides consistent evidence that garlic powder intake reduces the CVD risk factors of TC, LDL-C, FBG and BP.